IDENTIFICATION OF FACTORS CAUSING DRIVER’S DISTRACTION IN OMAN - Javid, Muhammad Ashraf; Al-Neama, Mustafa Yousif (Journal of Applied Engineering Science, 2018)
In recent years the economic and infrastructure development have led to increase the number of private vehicles on the roads in Oman. The increased motorized traffic tends to increase the roadside accidents that results in fatalities and injuries. To ensure safe mobility of the citizens, it is very important to evaluate the underlying factors that contribute towards the occurrence of accidents so that proper countermeasures can be developed and implemented. The main objective of this study was to identify the most significant driver’s distraction factors through a questionnaire survey and suggest some policy measures. The designed questionnaire was consisted of personal and driving attributes, and potential internal and external factors that cause distraction to the drivers. This questionnaire survey was conducted at some feasible locations in Muscat and Nizwa city with drivers of different vehicles. The results of 252 collected samples showed that the use of mobile phone, eating while driving and presence of passengers in vehicle are the most significant internal distraction factors. Significant external factors included looking at the scenic elements, advertisement boards and other drivers. It was predicted that cell phone, interaction, and disturbance-oriented factors are significant determinants of driver’s propensity to be involved in an accident. This study proposed some behavioral intervention techniques that need to be considered for the improvement of traffic safety in Oman.